2014
DOI: 10.1016/j.bioelechem.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Disassembly of actin structures by nanosecond pulsed electric field is a downstream effect of cell swelling

Abstract: Disruption of the actin cytoskeleton structures was reported as one of the characteristic effects of nanosecond-duration pulsed electric field (nsPEF) in both mammalian and plant cells. We utilized CHO cells that expressed the monomeric fluorescent protein (mApple) tagged to actin to test if nsPEF modifies the cell actin directly or as a consequence of cell membrane permeabilization. A train of four 600-ns pulses at 19.2 kV/cm (2 Hz) caused immediate cell membrane poration manifested by YO-PRO-1 dye uptake, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 43 publications
6
56
0
Order By: Relevance
“…Using live-cell imaging we demonstrated that permeabilisation does not occur across the entire cell membrane, as YO-PRO-1 showed a polar entry and then diffused across the cell, in agreement with a previous study using 600 ns pulses31.…”
Section: Discussionsupporting
confidence: 91%
“…Using live-cell imaging we demonstrated that permeabilisation does not occur across the entire cell membrane, as YO-PRO-1 showed a polar entry and then diffused across the cell, in agreement with a previous study using 600 ns pulses31.…”
Section: Discussionsupporting
confidence: 91%
“…Assuming that the electric field is not be distorted, the cell thickness should be sufficiently thin compared with the glass, and the dielectric constant of cell is almost equal to that of glass (ϵ r ≈ 4–5, borosilicate glass), the electric field along z‐axis (E z ) applied to the adherent cell should be calculated from V p and the thickness of dishes. Because the thickness of dishes used in this study was about 0.20–1.0 mm, the estimated intensity of the E z transiently applied to the adherent cells was 30–150 kV/cm at a maximum and could affect the cell membrane structure and cellular activities …”
Section: Resultsmentioning
confidence: 99%
“…Cell culture methods, nsEP generation and delivery to cells, dosimetry, and image acquisition and processing were essentially the same as reported earlier [6,15,37,39] and will only be described in brief here. A novel method of calibrating the emission of DNA stains against their concentrations is introduced and discussed in section 3.2 under "Results".…”
Section: Methodsmentioning
confidence: 99%
“…The exposure procedures were similar to those described recently [6,15,39,40]. Nearly rectangular 60- or 600-ns pulses were generated in a custom-made transmission line circuit.…”
Section: Methodsmentioning
confidence: 99%